A retrospective study of iRoot BP Plus pulpotomy compared with Vitapex pulpectomy for irreversible pulpitis of primary molars with the presence of coronal pulp tissue. Issue 2 (13th December 2022) - Hu, Xiaoyan; Liang, Zhaojia; Wang, Qun; Liu, Laikui
Abstract: Background: Pulpotomy has been successfully performed in immature and mature permanent teeth with irreversible pulpitis but rarely in primary teeth. Aim: To evaluate the outcomes of iRoot BP Plus pulpotomy and Vitapex pulpectomy in primary molars with irreversible pulpitis. Design: We selected 130 primary molars of 99 patients, aged 3–7 years, diagnosed with irreversible pulpitis with coronal pulp tissue and treated with iRoot BP Plus pulpotomy or Vitapex pulpectomy (median follow‐up period: 18 months). They were divided into the pulpotomy ( n = 88) and pulpectomy ( n = 42) groups according to treatment procedure. The pulpotomy group was further divided into asymptomatic ( n = 46) and symptomatic ( n = 42) subgroups according to preoperative symptoms. The chi‐squared test and Cox regression were performed to analyze the outcomes. Results: Clinical and radiographic success rates were significantly higher in the pulpotomy group (98.9% and 95.5%) than in the pulpectomy group (88.1% and 54.8%) and did not differ significantly between asymptomatic and symptomatic pulpotomy subgroups. Conclusion: Irreversible pulpitis of primary molars with coronal pulp tissue can be successfully treated with iRoot BP Plus pulpotomy. Early intraradicular resorption of materials is the main adverse outcome of Vitapex pulpectomy.